The Relationship of the heat of hydration to the bored pile integrity of bored piles contaminated with soil during setting - Armes, Jowena Roselle Q.; Mojica, Marlon Vince J.; Acacio, Alexis Philip A. (Quezon City College of Engineering, University of the Philippines Diliman, 2014)
Cast-in-place bored piles are the most popular used pile foundations for bridges, piers and tall structures having heavy loads. The current methodology in pile testing during construction of bored piles is costly and can only be done 28 days after the pouring of concrete. The aim of this study is to device an alternative bored pile testing plan to better detect faulty piles. Also, to have an alternative method that can detect faulty piles earlier than the current standard for testing. This would help in earlier remedial of plans. In this study, LM35 temperature sensors were used to measure the heat of hydration of the concrete. Temperature readings were observed every two hours for three days. The results showed that there was a difference of 8°C between the areas contaminated with soil and areas with pure concrete. The contamination was detected in as early as twelve hours from pouring.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Piling (Civil engineering) -- Testing